Auxinic herbicides and glyphosate inhibit horseweed seed production and germination - Novello, Bruna D. [UNESP]; Barroso, Arthur A. M.; da Silva, Diecson R. O.; Bacha, Allan L. [UNESP]; Roncatto, Eduardo; Albrecht, Alfredo J. P. (My University, 2025)
Background: Horseweed (Conyza bonariensis) is an important weed species infesting soybean plantations. Some biotypes with multiple herbicide resistance have been recently reported. One way to avoid weed dispersion and spread to adjacent areas is by reducing and preventing seed germination. Objective: We aimed to evaluate the effects of auxinic herbicides (2,4-D, dicamba, triclopyr and halauxifen-methyl), with or without mixing with glyphosate, on the production, germination and morphology of horseweed seeds. Methods: With the recent release of the transgenic soybean event DAS-44406-6 in Brazil, we conducted three experiments with different horseweed biotypes (Canguiri, Palotina and Palmeira) and application stages (early and late vegetative, and early reproductive). Results: Auxinic herbicides, applied alone or mixed with glyphosate, reduced the germination and production of horseweed seeds, regardless of the stage of application. The application of herbicides caused morphological changes in the seeds, such as darkening, damaged achenes and papillae, and absence of embryos. Conclusions: For plants that produced seeds, there was a 100% reduction in germination, showing that the application of these herbicides can be a viable strategy in the integrated management of this species.
Keywords: Conyza bonariensis; Dicamba; Halauxifen-Methyl; Seed Viability; Triclopyr